Relevance of Taisir al-Khallaq Moral Education Methods to MI Akidah Akhlak Teacher Guidebooks - Elis Siti Julaihah; Nur Hafni Amalia (Smart: Journal of Global Islamic Studies and Social Science, 2026)
Modernization triggers massive global moral degradation, challenging fundamental educational foundations. Specifically, Islamic primary schools struggle to effectively internalize ethical values using classical scriptures. Previous studies merely cataloged traditional moral contents without addressing their pedagogical translation into modern curricula. This study examines the epistemological reconstruction of moral education methods from the classical Taisir al-Khallaq text into the Grade One Akidah Akhlak teacher guidebook. Findings indicate that classical approaches, including advice, modeling, habituation, and eschatological warnings, are effectively adapted into concrete, interactive, and socio-pragmatic instructional practices suitable for early childhood specific cognitive developmental stages. As a novelty, this research reveals a dialectical convergence rather than a methodological clash, proving traditional esoteric doctrines successfully transform into modern embodied learning practices. Ultimately, these outcomes offer significant practical implications by establishing a transformative pedagogical framework, ensuring classical Islamic literature maintains absolute relevance and high adaptability for strengthening contemporary primary character education against global moral disruption.